2007
DOI: 10.1200/jco.2007.10.8936
|View full text |Cite
|
Sign up to set email alerts
|

Statins and the Risk of Colorectal Cancer: A Meta-Analysis of 18 Studies Involving More Than 1.5 Million Patients

Abstract: Our meta-analysis results do not support the hypothesis that statins strongly reduce the risk of colorectal cancer, when taken for management of hypercholesterolemia. However, we cannot rule out a modest reduction in risk or an effect associated with higher doses of statins.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
107
1
2

Year Published

2007
2007
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 127 publications
(117 citation statements)
references
References 51 publications
7
107
1
2
Order By: Relevance
“…A chemopreventive effect on colonic neoplasms by metformin, TZDs, lowdose aspirin, and NSAIDs has been suggested in epidemiologic trials (10-13); however, insulin therapy is associated with the development of colorectal cancer (14). Although a significant chemopreventive effect of statins against colon neoplasm was found in the current study, meta-analysis results failed to support this effect in patients on statin therapy (38).…”
Section: Discussioncontrasting
confidence: 55%
“…A chemopreventive effect on colonic neoplasms by metformin, TZDs, lowdose aspirin, and NSAIDs has been suggested in epidemiologic trials (10-13); however, insulin therapy is associated with the development of colorectal cancer (14). Although a significant chemopreventive effect of statins against colon neoplasm was found in the current study, meta-analysis results failed to support this effect in patients on statin therapy (38).…”
Section: Discussioncontrasting
confidence: 55%
“…I do not expect that statins would protect against only prostate cancer; their actions are quite diverse. On the other hand, the same consistency of findings between statins and the incidence of cancer overall (12,17,30) or lung (30), breast (31), colorectal (32), and hematologic (33) cancers has not been observed.…”
Section: )mentioning
confidence: 61%
“…11 According to another meta-analysis of 18 published studies, there was no association between statin use and risk of colorectal cancer found in either randomized controlled studies (n 5 6) or prospective cohort studies (n 5 3). 12 However, the meta-analysis of retrospective case-control studies (n 5 9) indicated a statistically significant association between statin use and a modest reduction in the risk of colorectal cancer.…”
Section: Statin and Cancer Chemopreventionmentioning
confidence: 99%